Implementation of Physical Education Learning K-13 Class 11 Semester I in Senior High School (Department of Physical Education, Sport, Health and Recreation, 2018)
The purpose of this study was to investigate the implementation of physical education learning based on the 2013 Curriculum in the 11th grade at Senior High Scholl â€œSMAN 8 Malangâ€. The method used in this research was non-experimental research design in the form of descriptive survey. The subjects used were 3 physical education teachers as well as 110 students of 11th graders, and there were 10 students taken from each class. The sampling technique used was proportionate sampling. The instruments used for collecting data were observation techniques, questionnaires, interviews and documentation. Meanwhile, the technique used to analyze the data was qualitative descriptive. From the results obtained of the questionnaires, it was found that only 88% the acquisition of the physical education learning based on the 2013 Curriculum was used, while 12% were not implemented. Suggestion that could be given to the teacher was teaching physical education should be given in accordance to the 2013 Curriculum as a whole.